Updating the taxonomy of the ant genus Myrmecina (Hymenoptera, Formicidae) in China with descriptions of three new species - Liu, Cong; Fischer, Georg; Liu, Qing; Peng, Yan-Qiong; Economo, Evan P.; Guénard, Benoit (Zootaxa, 2022)
In this study, we present a taxonomic update for the ant genus Myrmecina in China that includes 14 species in total. A recent survey of the leaf litter ant fauna in China’s Hengduan Mountains collected three unknown Myrmecina species, which we describe here as Myrmecina eowilsoni sp. nov., M. gaoligongensis sp. nov., and Myrmecina pierceae sp. nov. These new species are clearly distinguishable from all the other species in the genus. We provide an update to the identification key of Chinese Myrmecina, as well as a diagnostic discussion and high-quality specimen images. In addition, Myrmecina raviwonghei Jaitrong, Samung, Waengsothorn & Okido 2019 is reported for the first time from China.